Bacterial colonization of medical equipments: A surveillance study of NICU and PICU instruments - Kandwal, Priya; Dr. Reshmi Roy; K Rana, Sudhir; S Mahawal, Bhim (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Health care associated infection in intensive care unit is a challenging issue worldwide. Fomites and inanimate objects/equipment may be contaminated by various pathogenic microorganisms by the health care worker. Therefore, could be potential risk factor for the critical ill patients of neonatal and pediatric intensive care units (NICUs &PICUs). The present study was carried out to examine the bacterial colonization from equipments of pediatric and neonatal ICUs. Materials and methods: A total of 260 specimens were collected within a period of six months from the instruments/hands and nasal swabs of health care workers using moisten (0.9% w/v physiological saline) sterile cotton swab. Samples were processed according to standard protocol. Result: In the current study, the most prevalent organism on the surface of medical devices of PICU were CoNS (16.66%) and S.aureus (16.66%) while in NICU the most prevalent organism was Klebsiella spp (11.25%) followed by A. baumanni (10%), E.coli (2.5%), CoNS (6.25%), S. aureus (6.25%) and E. faecalis (6.25%). Conclusion: The study highlights the importance of surveillance of risk factors of hospital acquired infection and strategic implantation of preventive measures in critical care units.